Hepatitis B Seroprevalence and Associated Factors Among Inpatients From 2014 to 2023: A Single-Centre Retrospective Study in a Malaysian Tertiary Hospital - Kamaluddin, Nurul Asyikin; Abdullah, Nurzulaikha; Lee, Yeong Yeh; Wong, Mung Seong; Draman, Nani; Mustaffa, Nazri (Malaysian Journal of Medical Sciences, 2026)
Background: Hepatitis B virus (HBV) remains a global health burden, causing significant health problems, including morbidity and mortality. The World Health Organization (WHO) aims to reduce new infections by 90% and deaths by 65% by 2030, with a focus on the Western Pacific and Southeast Asia. In Malaysia, HBV incidence rose from 2.26 per 100,000 in 2010 to 12.65 per 100,000 in 2015, classifying the country as having an intermediate burden with a seroprevalence of 1.5% to 9.8%. The major transmission routes include perinatal transmission, blood exposure, sexual contact, and needle sharing. This study aimed to provide insight into the epidemiology and disease burden of HBV in a large tertiary hospital in Malaysia. Insights from this study will assist in future directions regarding public health strategies to reduce the burden of hepatitis B by 2030. Methods: This study investigated the seroprevalence of hepatitis B infection (HBsAg) among inpatients at Hospital Universiti Sains Malaysia over 10 years from 1 January 2014 to 31 December 2023. This retrospective study included patients who underwent HBsAg screening during ward admission. Subjects were selected based on probability sampling after reviewing the inclusion and exclusion criteria. Descriptive and inferential analyses were performed following data collection. Statistical significance was determined by P-values using IBM SPSS version 29. Results: A total of 308 patients were identified. The overall seroprevalence was 9.1% (95% CI: 0.06, 0.12), with annual rates fluctuating between 6.3% and 10.7%. The highest positivity rate was observed in the 45 to 54 age group (14.3%), whereas the lowest positivity rate was observed in those aged > 64 years (5.0%). Males exhibited a higher positivity rate (11.7%) than females (6.5%). Private employees had the highest positivity rate (28.6%) among the occupational groups. Individuals coinfected with HIV had a strikingly high positivity rate of 62.5%. Our analysis identified needle sharing as a significant risk factor, with an adjusted odds ratio of (OR = 8.87; 95% CI: 1.64, 47.91; P = 0.011). Other risk factors, such as family history of chronic hepatitis, multiple sexual partners, history of blood transfusions, and body tattooing, showed increased odds but were not statistically significant. Conclusion: Our study provides insights into the local epidemiology, the burden of hepatitis B infection, and the factors that contribute to disease transmission. This study highlights the need for targeted public health interventions to reduce risk behaviours, particularly needle sharing, to control the spread of hepatitis B in the region.